Sexual dichromatism, size dimorphism, and microscale anatomy of white wing stripe in blue tits. Issue 6 (1st February 2021) - Janas, Katarzyna; Gaweł, Paulina; Łatkiewicz, Anna; Lutyk, Dorota; Gustafsson, Lars; Cichoń, Mariusz; Drobniak, Szymon M
Abstract: Achromatic patches are a common element of plumage patterns in many bird species and there is growing body of evidence that in many avian taxa they can play a signaling role in mate choice. Although the blue tit Cyanistes caeruleus is a well-established model species in the studies on coloration, its white wing patch has never been examined in the context of sex-specific trait expression. In this exploratory study, we examined sexual size dimorphism and dichromatism of greater covert's dots creating white wing patch and analyzed its correlations with current body condition and crown coloration—a trait with established role in sexual selection. Further, we qualitatively analyzed microstructural barb morphology underlying covert's coloration. We found significant sexual dimorphism in the dot size independent of covert size and sexual dichromatism in both white dot and blue outer covert's vane spectral characteristics. Internal structure of covert barbs within the white dot was similar to the one found in barbs from the blue part that is, with a medullary area consisting of dead keratinocytes containing channel-type ß-keratin spongy nanostructure and centrally located air cavities. However, it lacked melanosomes which was the main observed difference. Importantly, UV chroma of covert's blue vane was positively correlated with crown UV chroma and current condition (the latter only in males), which should be a premise for further research on the signal function of the wing stripe.